THE ANALYSIS OF TEACHER’S INTERACTION BY USING SELF-EVALUATION TEACHER TALK (SETT) IN SMPN 13 SURABAYA - Alfan Hariri; Rizka Safriyani; Zulidyana D. Rusnalasari (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
In teaching, teacher do not only think about the pedagogic goals, material, and activity used. At the same time, the teacher should also think about how effective the interaction used linked to the pedagogic goals. In short, the success of the teaching learning process relies on how the teacher’s interaction in leading the students to achieve the pedagogic goals. From those phenomenon, this thesis analyzes the suitability of teacher’s interaction with the pedagogic goals in teaching English lesson in SMPN 13 Surabaya by using SETT. The research object is an English teacher of SMPN 13 Surabaya who teach in two different classes; A and G 7thgrade. This study practices qualitative method which uses SETT frame work as a means of analysis. In addition, the researcher uses voice recording and interview as a technique to get the data. As a result, the teacher’s interaction is in the form of IRF pattern that mostly uses close question as initiation. In addition, the teacher’s interactional features that often occur is teacher echo, display question and confirmation request. Furthermore, the teacher’s interaction coincides with the SETT framework to lead student in gaining the pedagogic goals. Though, there are some part of interaction that can be improve for better student involvement such as extended wait time, teacher echo and way of scaffolding.